Carbon dioxide uptake from natural gas by binary ionic liquid–water mixtures1. Issue 8 (3rd August 2015) - Anderson, Kris; Atkins, Martin P.; Estager, Julien; Kuah, Yongcheun; Ng, Shieling; Oliferenko, Alexander A.; Plechkova, Natalia V.; Puga, Alberto V.; Seddon, Kenneth R.; Wassell, David F.
<x xml:space="preserve">Abstract</x> Carbon dioxide solubility in a set of carboxylate ionic liquids formulated with stoicheiometric amounts of water is found to be significantly higher than for other ionic liquid systems previously reported.